Internet, redes sociales y periodismo ciudadano en los jóvenes universitarios de Latacunga - Arroyo Rubio, Gissela Beatriz (2016)
The public is which endow of meaning to journalism work. Not only the professional of information journalism, conveniently titled and referee can live up to its requirements. Because, today it is recognized by all. For this reason, the present research work: "Internet, social networks and citizen journalism in university students of Latacunga" is formulate in order to determine the appropriate use that university students, give to the Internet and social networks to foment the citizen journalism. The relationship between citizen journalism, internet and social networks merit the application of a method of documentary bibliographical research. It was based with field research applied to a universe of 12,424 students of SCHOOL POLITECNICAL OF ARMY OF LATACUNGA (ESPE-L) and Technical University of Cotopaxi. It was through a probabilistic random sampling. We worked with 261 students that give an input data related to this social group in particular. It constitutes one of the most important users and consumers of the Internet and social networks. At the same time, it provides potential generators of information through digital journalism in the exercise of citizen journalism. At the end, the study provides interesting information regarding the use of social networks mainly the Facebook. This has enabled them to have varied and too much information that does not allow you to select or make a judgment to foment what it means the practice of citizen journalism.